The Influence of Organizational Culture & Training Programs on Employee Performance with Self-Efficacy as an Intervening Variable at the General Secretariat of the Ministry of Agrarian Affairs & Spatial Planning/National Land Agency - Ilham Pratama Noviandi; Yayan Hadiyat; Radjab Tampubolon (Universitas KH. Abdul Chalim Mojokerto, 2025)
This research was conducted to determine the influence of organizational culture and training programs on employee performance through self-efficacy, at the General Secretariat of the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency. This research was conducted within the General Secretariat of the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN). This research is expected to provide input for institutions to strengthen a more open and innovation-supporting organizational culture, improve the effectiveness of training programs to better meet employee needs, and build stronger employee self-efficacy, thus directly contributing to improved employee performance. In this study, sampling was conducted using the Simple Random Sampling method, distributing questionnaires to 163 employees. The data obtained from the questionnaires were then analyzed using SmartPLS software version 3 to test the formulated model of relationships between variables, namely organizational culture, training programs, self-efficacy, and employee performance. The research results indicate that organizational culture influences employee performance, training programs do not influence employee performance, and organizational culture and training programs affect self-efficacy. Self-efficacy does not influence employee performance, organizational culture does not affect employee performance through self-efficacy, and training programs do not influence employee performance through self-efficacy.